The Influence of Road Service Quality on Traffic Noise Levels - Lakawa, Irwan; Syamsuddin, Syamsuddin; Sudarta, Sudarta (International Journal of Management and Education in Human Development, 2024)
Traffic noise resulting from motor vehicles stands as a significant environmental concern in urban areas. Kendari, serving as the capital of Southeast Sulawesi Province and classified as a Major City in Indonesia, inevitably contends with the phenomenon of noise pollution. This research aims to analyze the influence of road service levels on traffic noise. The study reveals that the road service level along Ahmad Yani Street in Kendari has an average saturation degree of 0.27, classifying it as Level of Service (LoS) B. This reflects a stable traffic flow, though vehicle speeds are gradually reduced. Drivers still retain sufficient freedom in speed selection. Meanwhile, the average noise level on this road segment is measured at 73.6 dB, exceeding the environmental noise threshold stipulated by the Minister of State for the Environment of the Republic of Indonesia's Decree No. KEP-48/MENLH/11/1996. The influence of road service level on noise levels is quantified at 31.3%, with the remaining 68.7% attributed to unexamined factors within this study.